Seasonal Diversity and Population Status of Waterbirds in Phewa Lake, Pokhara, Nepal - Giri, Bikash; Chalise, Mukesh Kumar (Journal of Wetlands Ecology, 2008)
The study (2007-08) was carried out in Phewa Lake which is one of the largest lake systems in Nepal to evaluate seasonal diversity and population status of waterbirds. A total of 39 waterbird species belonging to 17 families of 5 orders was recorded. The highest number of species (31 species) was found in December and January. Winter was the most diverged season in terms of number of species (35 species) and summer and autumn by 17 species. January had the highest (1584) and September the lowest (345) waterbird population. Out of 39 species, 15 species were winter visitors, 10 resident, and 4 rare winter visitor. The highest diversity ( H =2.6228) was found in February and lowest ( H =1.2014) in June. The value of evenness (Jacob's coefficient) was higher (0.8485) in February and lowest (0.4555) in June. During June, 69.92% (616 individuals) of the total population (881) constituted only Cattle Egret. The dominancy was found highest (C=0.5058) in June and lowest (C=0.1020) in February. The bird communities of summer and autumn were more similar (S=0.7059) than the summer and winter (S=0.5). The fluctuation in number of individuals of bird species was found unrelated to seasons (months) (F=1.71, df = 8, 342, P ≤ 0.05). The species richness was found different in different seasons (months) (Χ2=29.34, df = 8, P ≤ 0.05). Detail study of bird diversity and population status with periodic monitoring in Phewa Lake is recommended for their conservation and management as a whole. Key Words: Phewa lake, wetland, waterbirds, diversity, population DOI: 10.3126/jowe.v1i1.1568 Journal of Wetlands Ecology Vol.1(1/2) 2008, p.3-7